Zn VA S KIRISHMA ATOMLARINI KREMNIYGA LEGIRLASHNING DIFFUZIYA USULINING MATEMATIK MODELI - Haqqulov, M.K.; Isakov, B.O.; Shakarov, F.Q.; Mahmudov, S.Y.; Sodiqova, F.O. (SCIENCE and SOCIETY, 2025)
This work is devoted to the mathematical modeling of the diffusion method of impurity Zn and S doped into silicon. In the work, a model of three different diffusion mechanisms was developed, and the results of the calculations showed that the diffusion of Zn first, then S dopants, is preferable in the formation of ZnS binary nanoclusters in silicon.